Robust links in photoactive covalent organic frameworks enable effective photocatalytic reactions under harsh conditions - Wang, Jia-Rui; Song, Kepeng; Luan, Tian-Xiang; Cheng, Ke; Wang, Qiurong; Wang, Yue; Yu, William W.; Li, Pei-Zhou; Zhao, Yanli (Nature communications, 2024)
Developing heterogeneous photocatalysts for the applications in harsh conditions is of high importance but challenging. Herein, by converting the imine linkages into quinoline groups of triphenylamine incorporated covalent organic frameworks (COFs), two photosensitive COFs, namely TFPA-TAPT-COF-Q and TFPA-TPB-COF-Q, are successfully constructed. The obtained quinoline-linked COFs display improved stability and photocatalytic activity, making them suitable photocatalysts for photocatalytic reactions under harsh conditions, as verified by the recyclable photocatalytic reactions of organic acid involving oxidative decarboxylation and organic base involving benzylamine coupling. Under strong oxidative condition, the quinoline-linked COFs show a high efficiency up to 11831.6 μmol·g −1 ·h −1 and a long-term recyclable usability for photocatalytic production of H 2 O 2 , while the pristine imine-linked COFs are less catalytically active and easily decomposed in these harsh conditions. The results demonstrate that enhancing the linkage robustness of photoactive COFs is a promising strategy to construct heterogeneous catalysts for photocatalytic reactions under harsh conditions. The development of heterogeneous photocatalysts applicable under harsh conditions is challenging. Here the authors report the conversion of imine linkages into quinoline groups in triphenylamine incorporated photosensitive covalent organic frameworks to develop robust heterogeneous photocatalysts for photocatalytic applications in harsh conditions.